2022
DOI: 10.3390/coatings12091241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of PVP on Thermal, Mechanical, and Dielectric Properties in PVDF-HFP/PVP Thin Film

Abstract: In this research, the influences of the addition of PVP to PVDF-HFP polymers and the preparation of thin films using a solvent casting method were studied. The PVDF-HFP and polymer blend PVDF-HFP/PVP thin films with a nanostructured surface were investigated using scanning electron microscopy, differential scanning calorimetry, nanoindentation, and dielectric spectroscopy. The results showed that the PVP formed a dispersed phase (the poorer conductive islands) in the PVDF-HFP polymer matrix, which reduced its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This value is comparable with the X C measured for various PVDF‐HFP films recently reported in the literature. [ 43,49,51 ] The X C of the PVDF‐HFP films filled in Fe NPs up to 10 mg is lower than the X C found for the bare PVDF‐HFP film and the PVDF‐HFP film filled in 50 mg Fe NPs. This might be related to the fact that the nanoparticles in small amounts tend to form smaller agglomerations than the nanoparticles in high amounts which penetrate better the copolymer films.…”
Section: Resultsmentioning
confidence: 85%
“…This value is comparable with the X C measured for various PVDF‐HFP films recently reported in the literature. [ 43,49,51 ] The X C of the PVDF‐HFP films filled in Fe NPs up to 10 mg is lower than the X C found for the bare PVDF‐HFP film and the PVDF‐HFP film filled in 50 mg Fe NPs. This might be related to the fact that the nanoparticles in small amounts tend to form smaller agglomerations than the nanoparticles in high amounts which penetrate better the copolymer films.…”
Section: Resultsmentioning
confidence: 85%
“…The degree of crystallinity based eq 3 is usually used for semicrystalline polymers where there is a clear distinction between the crystalline and amorphous regions . Crystallized polymers simply consist of aligned polymer chains, forming lamellae. , According to previous studies, eq 3 was only used to determine the degree of crystallinity of poly­(vinylidene fluoride) (PVDF) although it did consist of many other materials. , In other previous studies, eq 3 has been used to calculate the degree of crystallinity of several composite polymers, i.e., poly­(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP), poly­(ethylene oxide)/poly­(vinyl pyrrolidone) (PEO/PVP-TiO 2 ), polyvinyl alcohol (PVA), , polyethylene-oxide/poly­( l -lactide) (PEO/PLLA), and polyetheretherketone (PEEK) . Additionally, the previous research also showed that the degree of crystallinity in DSC was only analyzed for the effect of the polymer (PVA), while the degree of crystallinity of the red betel extract was calculated on the XRD section .…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the molecular weight and structure (i.e., the arrangement of the pendant groups, pyrrolidone, and amide groups), it was reported that the T g of PVP and PAM could vary from 54 C to 175 C and 100 C to 184 C, respectively, 44,45 and our work is consistent with these reports. For example, Jia et al 46 and Centa et al 47 reported a glass transition temperature of 61.8 C and 164.8 C for PVP polymers respectively. The optimized blended films also exhibited a T g of 83.63 C, lower than the T g of the parental polymers.…”
Section: Thermal Characteristicsmentioning
confidence: 99%